2019
DOI: 10.1109/tit.2019.2899868
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Bounds and Constructions of Codes in the Generalized Cayley Metric

Abstract: Permutation codes have recently garnered substantial research interest due to their potential in various applications, including cloud storage systems, genome resequencing, and flash memories. In this paper, we study the theoretical bounds and constructions of permutation codes in the generalized Cayley metric. The generalized Cayley metric captures the number of generalized transposition errors in a permutation, and subsumes previously studied error types, including transpositions and translocations, without … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The constraint of σ being minimal indicates that d B (π 1 , π 2 ) = d if and only if d + 1 is the minimum number of segments that π 1 needs to be divided into for such an operation. This definition is somehow not intuitive enough and thus Yang et al [16] found another way to characterize the block permutation distance explicitly by the characteristic set of a permutation. Definition 2.3.…”
Section: Block Permutation Metricmentioning
confidence: 99%
See 4 more Smart Citations
“…The constraint of σ being minimal indicates that d B (π 1 , π 2 ) = d if and only if d + 1 is the minimum number of segments that π 1 needs to be divided into for such an operation. This definition is somehow not intuitive enough and thus Yang et al [16] found another way to characterize the block permutation distance explicitly by the characteristic set of a permutation. Definition 2.3.…”
Section: Block Permutation Metricmentioning
confidence: 99%
“…The block permutation metric can be characterized by the characteristic set and then some basic properties of the metric can be derived. These are summarized in the following two lemmas proposed in [16]. Lemma 2.4.…”
Section: Block Permutation Metricmentioning
confidence: 99%
See 3 more Smart Citations